PENGARUH KOMPENSASI NON FINANSIAL DAN KOMPETENSI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BPR TRIDARMA PUTRI - Ida Ayu Gede Kusuma Dewi; I Wayan Sukadana; I Wayan Suarjana (EMAS, 2022)
Rural Banks (BPR) are banks that carry out business activities conventionally or based on sharia principles which in their activities do not provide services in payment traffic. This study aims to determine and analyze the effect of non-financial compensation and competence on job satisfaction of employees at PT. BPR Tridarma Putri. This research was conducted at PT. BPR Tridarma Putri which is located at Jalan Diponegoro, No.25 Semarapura Kelod Kangin, Klungkung, Bali with research objects on non-financial compensation, competence and job satisfaction. The population in this study were 55 employees of PT. BPR Tridarma Putri. The sample of this study was determined by the population method, so the number of samples was 55 people. The data analysis technique is multiple linear regression analysis with the help of SPSS 25 Statistics to test and prove the research hypothesis. The results of the study of non-financial compensation and competence have a significant and partially positive effect on job satisfaction at PT. BPR Tridarma Putri, Klungkung.